Fundamentals of multimedia - Li, Ze-Nian; Drew, Mark S.; Liu, Jiangchuan (New York Spinger, 2014)
Contents: Introduction and multimedia data representations; multimedia data compression; multimedia communications and networking; multimedia information sharing and retrieval.
Includes bibliographical references and index
Keywords: Công nghệ thông tin